Inhibition of ATP release from Erythrocytes: A role for EPACs and PKC - Adderley, Shaquria P. (2011)
OBJECTIVE: Here we demonstrate that, in human erythrocytes, increases in cAMP that are not localized to a specific receptor-mediated signaling pathway for ATP release can activate effector proteins resulting in inhibition of ATP release. Specifically we sought to establish that exchange proteins activated by cAMP (EPACs) inhibit ATP release via activation of protein kinase C (PKC). METHODS: ATP release stimulated by iloprost (ILO), or isoproterenol (ISO), was determined in the absence and presence of selective phosphodiesterase inhibitors and/or the EPAC activator, 8CPT2OMecAMP (8CPT). To determine whether EPACs inhibit ATP release via activation of PKC, erythrocytes were incubated with phorbol 12-myristate 13-acetate (PMA) prior to either forskolin or ILO in the absence and presence of a PKC inhibitor, calphostin C (CALC). RESULTS: Selective inhibition of PDEs in one pathway inhibited ATP release in response to activation of the other cAMP-dependent pathway. 8CPT and PMA inhibited both ILO- and ISO-induced ATP release. Inhibition of ATP release with 8CPT was rescued by CALC. CONCLUSION: These results support the hypothesis that cAMP not localized to a specific signaling pathway can activate EPACs which inhibit ATP release via activation of PKC and suggest a novel role for EPACs in erythrocytes.